Solve for t 3t+3=4t

Math
3t+3=4t
Move all terms containing t to the left side of the equation.
Tap for more steps…
Subtract 4t from both sides of the equation.
3t+3-4t=0
Subtract 4t from 3t.
-t+3=0
-t+3=0
Subtract 3 from both sides of the equation.
-t=-3
Multiply each term in -t=-3 by -1
Tap for more steps…
Multiply each term in -t=-3 by -1.
(-t)⋅-1=(-3)⋅-1
Multiply (-t)⋅-1.
Tap for more steps…
Multiply -1 by -1.
1t=(-3)⋅-1
Multiply t by 1.
t=(-3)⋅-1
t=(-3)⋅-1
Multiply -3 by -1.
t=3
t=3
Solve for t 3t+3=4t

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top